Awake venovenous extracorporeal membrane oxygenation and survival - Rottmann, Felix A.; Zotzmann, Viviane; Supady, Alexander; Noe, Christian; Wengenmayer, Tobias; Staudacher, Dawid L. (Frontiers in Medicine, 2024)
Objectives Deep sedation on the ICU is linked to poor outcome. This study investigated the link between Richmond Agitation-Sedation Scale (RASS) and outcome in venovenous extracorporeal membrane oxygenation (V-V ECMO). Methods We performed a secondary analysis of a single-center V-V ECMO cohort. RASS was used as a surrogate measure of sedation depth, patients with a score ≥ −1 were considered awake. V-V ECMO durations below 24 h were excluded. Primary endpoint was 30-day survival. Secondary endpoints were hospital survival and weaning from both ventilator and ECMO therapy. Results A total of 343 patients were reanalyzed. The median age was 55 years and 52.2% (179/343) survived for 30 days after ECMO cannulation. Median duration of ECMO was 7.9 (4.7–15.0) days and the median duration of mechanical ventilation after ECMO cannulation was 11.8 (6.7–23.8) days. In the whole cohort, median RASS on day one and seven after ECMO were − 4 (−4 to −1) and − 3 (−4 to 0), respectively. ECMO survivors consistently had significantly higher RASS scores during the first 7 days of ECMO compared to non-surviving patients (p < 0.01). On day two after ECMO, survival of awake patients (i.e., RASS ≥-1) was significantly better compared to sedated [i.e., RASS −4 to −2; OR 2.20 (1.28–3.71), p < 0.01] or unresponsive patients [i.e., RASS -5; OR 2.27 (1.15–4.64), p = 0.02]. The survival benefit of awake ECMO was consistent from day two to seven. Patients awake at least once during ECMO showed higher 30-day survival rates [64.4% vs. 39.6%, OR 2.75 (1.77–4.24), p < 0.01]. Conclusion In this retrospective study, awake patients on V-V ECMO showed higher 30-day survival rates compared to sedated or unresponsive patients. These data should encourage further research on awake V-V ECMO.